Study on Environmental Management and Ecological Restoration of Coal Mine Wasteland - Jing Luo; Jingjing Liu; Qian Liu (Chemical Engineering Transactions, 2018)
The purpose of this study is to improve the ecological environment of coal mine wasteland and promote the transformation of coal industry. To this end, this paper studies the environmental management and ecological restoration of coal mine wasteland. Through reviewing the literatures, the relevant concepts were clarified. Then, combined with the experience of ecological restoration and landscape design in domestic coal mine wasteland, Huainan Coal Mine was taken as the research object, and ecological restoration and landscape design were conducted according to the coal mine location and the land use scale. This can help to realize the industrial landscape innovation of coal mine wastelands and the protection of natural ecological conditions, which is of great significance for balanced development of the natural ecology and human ecology in coal mine wastelands.